Exercise participation motives of Singapore university students - Lim, Fiona Qing Xue (2016)
The purpose of this study was to identify the important exercise participation motives in Singapore context and in particular among the university students. It was hypothesized that participation motives influence behaviour (exercise participation) by influencing behavioural regulations. 246 exercise participants (124 males, 122 females) aged 18 to 40 years old (M = 22.37, SD = 2.15) were included in the study. Participants filled up a survey instrument, which included validated measures of participatory motives, regulatory motives and exercise participation scores. A study description and informed consent were provided in accordance with Nanyang Technological University’s guidelines prior to survey administration. According to the final model, Enjoyment and Social Recognition motive had an indirect positive effect on Exercise Participation, Affiliation motive had an indirect negative effect on Exercise Participation, and Integrated Regulation and Strength and Endurance motive had a direct positive effect on Exercise Participation. Notably, enjoyment motive had a relatively significant role for exercise participation in this context. As for interventions to increase exercise participation, emphasis may be placed on enjoyment motive, social recognition motive, and strength and endurance motive. For social recognition motive, it may promote social media usage to fulfil the desire for positive recognition from others. Gradually, emphasis should be placed on intrinsic variables such as enjoyment to encourage long-term adherence. Future studies can look into the motives of sport participation as well as if there are any gender differences in motives for sport and exercise participation in Asian context.